29th AIAA Applied Aerodynamics Conference 2011
DOI: 10.2514/6.2011-3371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stall control by passive disturbance generators

Abstract: Passive low-aspect ratio cylinders mounted near the leading edge of an airfoil have been found to significantly improve the performance under dynamic stall conditions. In order to clarify the principle of operation these cylindrical disturbance generators (DG), high speed PIV and simultaneous pressure measurements have been performed on the pitching rotary aircraft wing profile OA209. Time resolved information for the flow field at mid chord and the pressure distribution was taken. In addition to the best conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…As shown by Lin [45], larger VGs create stronger streamwise vortices as compared to the submerged VGs and are expected to withstand the large adverse pressures during the dynamic stall process. The distance between pairs of VGs was selected to be 3.3 h (z0.1 c), as suggested by Heine et al [26]. No specific guidelines are available for the length of individual vane and the distance between each individual vane of the VGs.…”
Section: Vortex Generatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by Lin [45], larger VGs create stronger streamwise vortices as compared to the submerged VGs and are expected to withstand the large adverse pressures during the dynamic stall process. The distance between pairs of VGs was selected to be 3.3 h (z0.1 c), as suggested by Heine et al [26]. No specific guidelines are available for the length of individual vane and the distance between each individual vane of the VGs.…”
Section: Vortex Generatorsmentioning
confidence: 99%
“…It has generally been observed that an increase in the VG height can results in a decrease of the lift hysteresis [25]. Furthermore, VG configurations producing counterrotating streamwise vortices have been observed to be more beneficial for reducing the lift hysteresis compared to the configurations that produce co-rotating streamwise vortices [26]. However, these studies have also been limited to the light dynamic stall cases and, therefore, no indications can be made regarding the method's potency to reduce the DSV strength.…”
Section: Introductionmentioning
confidence: 97%
“…Figure (11) depicts the configuration and associated symbols used in Figs. (10), (13), and (14). In general, wing sweep reduces the lift curve slope and C Lmax since the airfoil "sees" only the wing perpendicular component of oncoming flow.…”
Section: B Wind Tunnel and Flow Visualization For Swept Configurationsmentioning
confidence: 99%
“…These studies have attempted to demonstrate the feasibility of sinusoidal leading-edges as passive flow control devices and have tried to quantify their effects. These studies have been both experimental [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and computational [16][17][18][19][20][21][22][23] in nature. Other studies [24][25][26][27] have focused on using the leading-edge sinusoidal modifications to reduce acoustical signatures of wings or fan blades.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, vortex generators (VGs) have been investigated as a potential dynamic stall control solution. [25][26][27][28] Active control approaches based on the (continuous or periodic) removal or addition of momentum to the boundary layer such as leading-edge suction, 29, 30 zero mass-flux excitation 19,31 and plasma actuators 32,33 have also been shown to reduce the adverse effects of dynamic stall. Relatively few attempts have been made to control dynamic stall by means of constant blowing.…”
Section: Introductionmentioning
confidence: 99%